2015 IEEE International Solid-State Circuits Conference - (ISSCC) Digest of Technical Papers 2015
DOI: 10.1109/isscc.2015.7063096
|View full text |Cite
|
Sign up to set email alerts
|

22.2 A 25Gb/s hybrid integrated silicon photonic transceiver in 28nm CMOS and SOI

Abstract: 5 contributed to this work while employed by Fujitsu Laboratories of America, Sunnyvale, CA Integrated photonic interconnect technology is free from the bandwidth-distance limitation that intrinsically exists in electrical interconnects, promising a disruptive alternative for next-generation scalable data centers. Silicon photonic platforms have been reported based on monolithic and hybrid integration. Monolithic systems mitigate integration overhead but require compromise in either electronic or photonic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Due to the potential compatibility of silicon photonics with the well-established industrialization methodologies used in CMOS technologies, there has been a significant thrust for monolithic integration of silicon photonics with electronics [85]. The additional parasitic capacitance and inductance of wirebonds or micro-bumps used by the hybrid electronic-photonic integrated circuit (EPIC) platforms [86]- [89] is minimized by Front-end-of-line (FEOL) integration of photonic components with electronics [30], [90]. Monolithic EPICs have a potential to meet the stringent power dissipation and aggregate throughput demands for short-to-long-range photonic interconnects [30], [44], [90].…”
Section: B Monolithic Silicon Photonics-electronics Co-integrationmentioning
confidence: 99%
“…Due to the potential compatibility of silicon photonics with the well-established industrialization methodologies used in CMOS technologies, there has been a significant thrust for monolithic integration of silicon photonics with electronics [85]. The additional parasitic capacitance and inductance of wirebonds or micro-bumps used by the hybrid electronic-photonic integrated circuit (EPIC) platforms [86]- [89] is minimized by Front-end-of-line (FEOL) integration of photonic components with electronics [30], [90]. Monolithic EPICs have a potential to meet the stringent power dissipation and aggregate throughput demands for short-to-long-range photonic interconnects [30], [44], [90].…”
Section: B Monolithic Silicon Photonics-electronics Co-integrationmentioning
confidence: 99%
“…Cignoli et al [53] presented a 25Gb/s MachZehnder-based transmitter with 275mW power consumption and 0.6mm 2 core area in 65nm bulk CMOS. Chen et al [51] developed a 25Gb/s hybrid integrated transceiver in 28nm CMOS and SOI with 123mW power consumption. Rakowski et al [56] proposed a 4×20gb/s ring-based hybrid CMOS silicon photonics transceiver with area of 3.3×2.4mm for 40nm LP CMOS transceiver chip and 6×4.5mm for 130nm SOI silicon photonic transceiver chip.…”
Section: Silicon Photonicsmentioning
confidence: 99%
“…After separating the modulated optical signals based on their wavelengths, PDs are used to detect each of the incoming signals. It has already been shown that MRR-based links are capable of operating at an excess of 25 Gb/s per wavelength [30], [53], [54], implying that a 25 Gb/s lane could be replicated as many times as needed to reach the aggregate goal. To relax the RX front-end design requirements to attain a 100 Gb/s throughput and beyond, the multiplexing factor (number of wavelengths, n) can theoretically be increased to a large extent [3].…”
Section: Towards a Power Efficient Tera-bit/s Linkmentioning
confidence: 99%